Aerobic α-hydroxylation of β-keto esters and amides by co-catalysis of SmI3 and I2 under mild base-free conditions. Issue 25 (22nd June 2016) - Yu, Shun-Ming; Cui, Kai; Lv, Fei; Yang, Zhen-Yu; Yao, Zhu-Jun
Graphical abstract: Highlights: Clean base-free α-hydroxylation of β-keto esters and amides with air. The first report of new binary catalytic system of SmI3 and I2 . Wide scope of substrates, excellent yields, and mild conditions. Both oxygen atoms of dioxygen are utilized and incorporated into the product through a unique free-radical process. Abstract: A clean base-free α-hydroxylation of β-keto esters and amides has been developed, in which air was used as the oxygen source and SmI3 and I2 were applied as the catalysts, affording the corresponding α-hydroxylated 1, 3-dicarbonyl products in good to excellent yields under mild conditions. Mechanism discussion shows that both oxygen atoms of dioxygen are utilized and incorporated into the product through a unique free-radical process.